PHYSIOTHERAPY MANAGEMENT OF ANKLE SPRAIN IN THE ACUTE PHASE: A CASE STUDY - Tristian, Deviana; Naufal, Adnan Faris; Maulana, Hakny Kusuma (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Ankle sprain is a condition in which the ligaments in the ankle are injured due to sprains. According to research, injuries to the ankle are less than 10% due to PTFL and CFL, and injuries in an inversion state or to the lateral ligaments of the foot occur in 85% of cases. The meta-analysis found that 13.6 occurred in female athletes and 6.94 occurred in male athletes per 1000 exposures to soccer, basketball, hockey, tennis, and other sports. In the problem of acute ankle sprains will cause symptoms of pain and swelling. Case Presentation: a case study of three databases (PubMed, Pedro, Science Direct) with the aim of knowing the effect of ultra sound, ice packs, exercise therapy and kinesio tape in The purpose of this paper is to influence the effect of giving ice, ultrasound, exercise, and kinesio tape in the acute phase of the right lateral ankle sprain patients.. The keyword used in the search was ankle sprain related to "acute phase exercise". Inclusion criteria were athletes who had a grade 1 ankle sprain and had no fractures. Management and Results: The use of ultrasound and ice packs can reduce pain intensity and can reduce edema, as well as the implementation of exercise therapy prescriptions and the use of kinesio taping can increase functional activity. Discussion: the study showed a decrease in silent pain from 5 to 3, tenderness from 8 to 6, and motion pain from 8 to 6. a decrease in edema from a difference of 3cm to 2cm, an increase in the functional activity of the FADI index, a decrease in the level of limitation after physiotherapy actions from 41.3% to 36.3%. Conclusion: physiotherapy management in the acute phase of ankle sprain cases uses a therapeutic program twice. Ultrasound, ice packs, exercise therapy, and kinesio tape are used to treat pain and swelling in ankle sprains.